A necessidade de uma compreensão hermenêutica e democrática do direito processual civil e o desvelar do caso concreto com a sentença liminar de mérito: a jurisdição-processual herdada e a jurisdição-processual a ser desenhada por uma filosofia no processo - Isaia, Cristiano Becker (Universidade do Vale do Rio dos Sinos, 2011)
This work discusses the limits and the possibilities to the conduction of civil process that disposes actually to meet the satisfaction locus of the social fundamental rights. It departures from the premise that the procedural-jurisdiction is immersed in a deficit of reality aimed given by the overvaluation of the knowledge process and its corollary ordinary-plenary-declaratory rite, that traditionally has keeping the process inside philosophy of consciousness and of political liberalism, raised the judge's consciousness and the obsession to the meet of certainties and eternal truths in de aling with individual subjective rights. For this reason it is necessary to project a hermeneutic and democratic understanding in the civil procedural law, which in this thesis has as its background the statement of a new post-bureaucratic process summarized (called preliminary ruling-sentence on the merits), steeped in a philosophy that justifies its existence for a historic-social time, breaking with conceptualism and reductionism procedural-dogmatic to meet constitutionally correct answers, taking the resurrection of the concrete case (and, as consequence, the revaluation of language) a condition of possibility. It is the attempt to clean the civil procedural law since juridical, historical, political and philosophical approaches, requirement outlined by the Democratic State of Law in his desire to break free of rationalist seduction, as it strives for consistency and integrity of judicial decisions. Th is work, in short, refers to a critical look at the juridical phenomenon since the use of a philosophy in right (using the bias provided by the understanding of philosophical hermeneutics) and its relation to a civil procedural stigmatized by modern proceduralistic, abandoning the metaphysical baggage of extracting meaning of the law resulting from the predominance of the method to overcome the ritualized and ineffective procedural model to the protection of fundamental social rights.
Keywords: Processo civil; Hermenêutica; Democratização; Sentença liminar; Direitos sociais-fundamentais; Civil process; Hermeneutics; Democratization; Preliminary sentence; Social fundamental rights; ACCNPQ::Ciências Sociais Aplicadas::Direito